Non-IgE-mediated gastrointestinal food allergy in children. Diagnostics, differential diagnostics, tactics of diet therapy - S. G. Makarova; T. E. Lavrova; G. A. Novik (Лечащий Врач)
In routine pediatric practice, non-IgE-mediated forms of gastrointestinal food allergy are still poorly recognized. This is due to the variety of clinical manifestations, the lack of reliable laboratory diagnostic methods, the unclear association with time, and the causal relationship with the allergen. Immature barrier mechanisms and early transition to formula feeding increase the penetration of allergen proteins, leading to sensitization. The article discusses three clinical forms of non-IgE-mediated gastrointestinal food allergy in children: food protein-induced enterocolitis syndrome, food protein enteropathy, and food protein-induced proctocolitis. In these cases, diet is a universal diagnostic and therapeutic measure. Eliminating the allergen allows for immunological reset and the induce the food tolerance. Therefore, strict adherence to elimination diets is crucial. The article also provides a differential diagnosis based on the level of allergic inflammation of the intestine and outlines principles and protocols for diagnostic and elimination diets.